Personnel management on the production line using the FlexSim simulation environment - Krynke, Marek (Manufacturing Technology Journal, 2021)
The article presents new possibilities of simulation software and its application to improve the pro-duction structure. In many enterprises, the basic issues are related to the determination of planned tasks for individual positions, calculating the demand for employees, taking into account their skills and qualifications, calculating work costs, determining work efficiency and its dynamics. Therefore proper work organization consists in setting the course of work in such a way as to obtain maximum results with the least amount of work by man and machine. The article presents the problem of per-sonnel allocation to the production line. The basic stages of developing a simulation model of this process are discussed, including all necessary information and inputs. The results shows impact of the selected simulation scenarios to the workload level of the staff and the duration of the production process. In this concept, to solve the problem a simulation model of the production process was built. A new generation of 3D FlexSim simulation environment with an integrated OptQuest optimi-zation module was used.
Keywords: Production Management; Simulation; Flexsim; Optimization; Performance Evaluation